2011
DOI: 10.5539/jms.v1n1p32
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Impacts of Online Banking Factors on Motivating the Process of E-banking

Abstract: Purpose -The purpose of this research paper is to explore and mature the Impact of selected factors on the customers' intention to use internet banking in Bahrain.Design/methodology/approach -This research based on an empirical study using a questionnaire with five-point Likert-scale, is applied to 171 usable responses. Three factors are tested, that is perceived usefulness (PU), perceived ease of use (PEOU), security and privacy (PC).Findings -Results indicate that all the elements for the three identified fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…The results of this research as shown in Table 7 indicate that there was positive and significant effect of the perceived credibility to intention to use. The http://www.ijmp.jor.br v. 9, n. 4, October -December 2018ISSN: 2236 results of this research in line with the results of Rahayu (2010) and Jalal et al (2011) which show that the perceived credibility has a positive and significant effect on the acceptance of ebanking. Each increase of 1 unit from the value of the perceived credibility (Y2) will increase 0.338 unit from the value of intention to use (Y3).…”
Section: Independent Journal Of Management and Production (Ijmandp)supporting
confidence: 88%
“…The results of this research as shown in Table 7 indicate that there was positive and significant effect of the perceived credibility to intention to use. The http://www.ijmp.jor.br v. 9, n. 4, October -December 2018ISSN: 2236 results of this research in line with the results of Rahayu (2010) and Jalal et al (2011) which show that the perceived credibility has a positive and significant effect on the acceptance of ebanking. Each increase of 1 unit from the value of the perceived credibility (Y2) will increase 0.338 unit from the value of intention to use (Y3).…”
Section: Independent Journal Of Management and Production (Ijmandp)supporting
confidence: 88%
“…Based on the positive intercorrelation, increasing level of education is supposed to increase web usage frequency (r=0,177). This finding was supported by the previous studies [39,40,4]. Hoffman and Novak [41] pointed the level of education as one of the effective factors in owning a computer and using web services in daily life processes along with some other factors.…”
Section: Web Usage and Securitysupporting
confidence: 74%
“…They refer education as "what counts", in order to emphasize the importance of it. Jalal, Marzooq & Nabi [39] and Bart, Shankar, Sultan & Urban [40] studied the motivating factors effecting online banking services. They attributed education as a significant factor among others.…”
Section: Web Usage and Securitymentioning
confidence: 99%
“…However, there are several theories and models in literature which have been employed to explain the relationships between the factors affecting the acceptance and adoption dominancy and user's attitude and willingness as shown in Appendix (1). Among them, there are three very well-known models which are the following: Technology Acceptance Model (TAM) by (Davis in 1989, Poon (2007), Aderonke A and Charles K. (2010), ), Jalal et al (2011), Johar and Awalluddin (2011, Abadi and Nematizadeh (2012), Ahmadi and Afrouzi (2012), Moga, et al (2012), Raida and Néji. (2013), El-Qirem (2013), Sanayei and Saneian (2013), Alikhani and Davarzani.…”
Section: The Applied Theories and Modelsmentioning
confidence: 99%